2014
DOI: 10.1016/j.scr.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Prostate progenitor cells proliferate in response to castration

Abstract: Androgen-deprivation is a mainstay of therapy for advanced prostate cancer but tumor regression is usually incomplete and temporary because of androgen-independent cells in the tumor. It has been speculated that these tumor cells resemble the stem/progenitor cells of the normal prostate. The purpose of this study was to examine the response of slow-cycling progenitor cells in the adult mouse prostate to castration. Proliferating cells in the E16 urogenital sinus were pulse labeled by BrdU administration or by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…The primary mechanisms for the conversion of ADPC into AIPC are variations in gene expression, signal pathway abnormity, dysregulation of proto-oncogenes, cancer suppressor genes and growth factors (4,5). Thus far, a number of relevant genes and signal pathways in CaP have been described (6).…”
Section: Introductionmentioning
confidence: 99%
“…The primary mechanisms for the conversion of ADPC into AIPC are variations in gene expression, signal pathway abnormity, dysregulation of proto-oncogenes, cancer suppressor genes and growth factors (4,5). Thus far, a number of relevant genes and signal pathways in CaP have been described (6).…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the castration-resistant cell types capable of regenerating prostate epithelium, a number of cell surface markers have recently been discovered that enrich for prostate stem cell activity including α2β1 integrin, CD49f, CD44, TROP2, CD133, CD117, CD338, and Sca-1 (mice only) (Garraway et al, 2010, Goldstein et al, 2010, Goldstein et al, 2008, Guo et al, 2012, Lawson et al, 2007, Lawson et al, 2010, Leong et al, 2008, Lukacs et al, 2010, Mulholland et al, 2009, Richardson et al, 2004, Shi et al, 2014, Xin et al, 2005, Xin et al, 2007). Fractions with these markers are enriched for cells that display increased clonogenicity, serial passaging as spheroids, and tissue regenerative capacity as xenografted recombinants with inductive urogenital sinus mesenchyme.…”
Section: Introductionmentioning
confidence: 99%
“…The primary reasons for ADPC becoming AIPC are gene expression variation, signal pathway abnormity, and dysregulation of proto-oncogenes, cancer suppressor genes and growth factors (4). At present, studies have identified a large number of relevant genes and signal pathways of prostate cancer (5)(6)(7). However, since the biological behavior of prostate cancer is extremely complex, any of the aforementioned hypotheses cannot clarify the pathogenetic mechanism of AIPC (6).…”
Section: Introductionmentioning
confidence: 99%